Air Pollution Management in North Macedonia - World Bank (World Bank, Washington, DC, 2019)
Air pollution is a significant problem in cities and urban centers in the Republic of North Macedonia. This report is one in a series of three reports on air quality management (AQM) in Bosnia and Herzegovina, Kosovo, and North Macedonia. It examines the nature and magnitude of ambient air pollution (AAP) in North Macedonia. It provides estimates of the health burden, and economic cost associated with the health impacts, of AAP, that is, particulate matter with a diameter of 2.5 micrometers or less (PM2.5) in North Macedonia. It also analyzes the roles of various sources of PM2.5 emissions on ambient air quality in North Macedonia at the national level. The institutional and policy framework for AQM in the country is examined, including contributions of other development institutions in supporting North Macedonia’s efforts to address air pollution. Furthermore, the report presents experiences of selected countries that have applied different policy, investment, and technical interventions for air pollution, prevention, reduction, and abatement. Finally, it provides recommendations for reducing air pollution in North Macedonia. People in North Macedonia and living in the Balkans and Eastern Europe are typically breathing more toxic particulate air pollution than their neighbors in Western Europe. This is due to fewer air pollution reduction policies and more solid fuel heating and cooking (meaning many more residential wood and coal stoves) in Eastern European and Balkan countries compared to the rest of Europe. Western Europe has mostly moved away from coal-fired power plants (or at least has pledged to reduce coal consumption to meet climate goals), but in the Balkans and in Eastern Europe they are still widely in use. In fact, the Balkan region is home to many coal and lignite-fired units and to 7 of the 10 most polluting coal-fired power stations in Europe.